(untitled) (Docentes 2.0 Journal, 2026)
The low levels of educational leadership motivated this research, which analyzes disruptive strategies to strengthen transformational leadership among early childhood education professionals. This study stems from the problems identified in public education centers throughout the country. The main objective was to develop disruptive strategies to enhance transformational leadership in early childhood education in Ecuador. The research was based on a systematic method, under the pragmatic paradigm and a mixed-methods approach, with a narrative-thematic design of a documentary, bibliographic, and cross-sectional nature. Valid and reliable evidence was obtained. The population consisted of 84 early childhood education teachers from preschools, who were selected through nonprobability sampling. Interviews and questionnaires were used as data collection techniques and instruments. Both were reviewed and validated by experts and underwent reliability testing using Cronbach’s alpha, with an average of 83%. These procedures yielded results that support the findings and demonstrate that applying disruptive strategies improves transformational leadership in early childhood education by 71% compared to the traditional model. The aim is to contribute to the scientific community with innovative proposals that strengthen academic performance by motivating and empowering teachers and improving the educational environment. Finally, it is recognized that school management is an essential component for increasing effectiveness and equity within the Education 3.0 framework.